Incidence and prevalence of type 1 diabetes and diabetic ketoacidosis in children and adolescents (0-19 years) in Thailand (2015-2020): A nationwide population-based study - Thanitsara Rittiphairoj; Maira Owais; Zachary J. Ward; Ché L. Reddy; Jennifer M. Yeh; Rifat Atun (Elsevier, 2022)
Summary: Background: There is a lack of published studies on incidence of type 1 diabetes (T1D) and diabetic ketoacidosis (DKA) in Thailand. We aimed to estimate the national prevalence and incidence of T1D and DKA. Methods: Using Thailand's nationwide population-based longitudinal data covering 69 million individuals, we included the entire children and adolescents recorded in the database. Diseases were identified using ICD-10 codes. We investigated the prevalence of T1D and cumulative incidence of T1D, T1D referral, DKA, and mortality risk of DKA in five years from 2015 to 2020. T1D and DKA annual incidence were also estimated. We present findings for the total population and by sex, age, and urban-rural residencies. Findings: A total of 19,784,781 individuals aged less than 20 years were identified in 2015. The crude T1D prevalence in 2015 was 17·6 per 100,000 and crude T1D incidence rate was 5·0 per 100,000. T1D prevalence and cumulative incidence were significantly higher in older children (p < 0·001) and females (p < 0·001) than their counterparts. Among those with T1D, cumulative incidence of T1D referral was 42·4%. It was highest amongst children aged 5-14 years and was significantly higher among females (all p < 0·05). The crude DKA incidence rate at any point after diagnosis was 10·8%. The cumulative incidence of DKA was significantly higher in females and peaked in individuals aged 5-14 years (all p < 0·001). The DKA mortality risk was 258·2 per 100,000. Interpretation: Older children and females had higher T1D prevalence. The DKA cumulative incidence and mortality risk were relatively low, and such incidence was peak in individuals aged 5-14 years. Funding: Harvard University.